Non-heme iron overload impairs monocyte to macrophage differentiation via mitochondrial oxidative stress - Cui, Yue; Gutierrez, Saray; Ariai, Sheller; Öberg, Lisa; Thörn, Kristofer; Gehrmann, Ulf; Cloonan, Suzanne M.; Naessens, Thomas; Olsson, Henric (Frontiers in Immunology, 2022)
Iron is a key element for systemic oxygen delivery and cellular energy metabolism. Thus regulation of systemic and local iron metabolism is key for maintaining energy homeostasis. Significant changes in iron levels due to malnutrition or hemorrhage, have been associated with several diseases such as hemochromatosis, liver cirrhosis and COPD. Macrophages are key cells in regulating iron levels in tissues as they sequester excess iron. How iron overload affects macrophage differentiation and function remains a subject of debate. Here we used an in vitro model of monocyte-to-macrophage differentiation to study the effect of iron overload on macrophage function. We found that providing excess iron as soluble ferric ammonium citrate (FAC) rather than as heme-iron complexes derived from stressed red blood cells (sRBC) interferes with macrophage differentiation and phagocytosis. Impaired macrophage differentiation coincided with increased expression of oxidative stress-related genes. Addition of FAC also led to increased levels of cellular and mitochondrial reactive oxygen species (ROS) and interfered with mitochondrial function and ATP generation. The effects of iron overload were reproduced by the mitochondrial ROS-inducer rotenone while treatment with the ROS-scavenger N-Acetylcysteine partially reversed FAC-induced effects. Finally, we found that iron-induced oxidative stress interfered with upregulation of M-CSFR and MAFB, two crucial determinants of macrophage differentiation and function. In summary, our findings suggest that high levels of non-heme iron interfere with macrophage differentiation by inducing mitochondrial oxidative stress. These findings might be important to consider in the context of diseases like chronic obstructive pulmonary disease (COPD) where both iron overload and defective macrophage function have been suggested to play a role in disease pathogenesis.